ANALYSIS OF CHEMISTRY GUIDES INTERGRATED DISCOVERY LEARNING MODEL AND CHARACTER FOR CLASS X SMA SEMESTER II - MASTIUR VERAWATY SILALAHI (LP2MTBM MAKARIOZ, 2020)
This research is a research and development (R&D). The purpose of this study is (1) to determine the feasibility level ofpracticum guides at publishers A, B and C, (2) to determine the feasibility level of integrated chemistry lab guides fordiscovery learning models and characters, and (3) the effectiveness of integrated chemistry lab guides for discovery learningmodels and characters for Class X High School. The research sample was taken by purposive sampling. The method used isdescriptive method. Data collection techniques using a questionnaire. Based on the results of data analysis and discussion, itcan be concluded that: (1) The level of eligibility of semester X semester II high school chemistry practice guides publishedby several publishers has a fairly decent category, but there are several components of the guide that need to be developed.,(2) The integrated chemistry practicum guide for discovery learning models and characters developed for SMA / MA class Xsemester II has a very feasible category, so it is feasible to be used in chemistry learning, and (3) The effectiveness of theintegrated chemistry practicum guide for discovery learning models and characters for student character is 85 , 23% with avery good category.